Sociological analysis of job satisfaction of working women at male-dominated workplace in Quetta (Balochistan) - Shabana Muhammad Anwar; Fateh Mohammad Burfat; Ameer Ali Abro (Journal of Management Practices, Humanities and Social Sciences, 2021)
The focus of the study is to examine the level of job satisfaction of working women in a male-dominant workplace. The women who work t male-dominated occupations faced several difficulties which decrease job satisfaction. The level of Job satisfaction can measure through the attitude of working women regarding work experiences. The present study was designed to investigate the influence of male dominancy on job satisfaction of working women at male-dominated work in Quetta city. The targeted population of this study was composed of N = 800 female workers from all higher educational institutes of Quetta (Balochistan). The sample size was N = 500. A structured questionnaire was developed to conduct primary data. The data were examined by using SPSS (statistical package for social sciences) version 24 software. The Chi-square test was implemented to measure the relationship between job satisfaction and male dominance at the workplace. The findings showed there is a significant association between male dominancy and job satisfaction of working women. The level of job satisfaction of working women is lower because of males’ supremacy. These findings imply that the chances of professional development must be equally provided to every worker without any gender disparity. Moreover, these findings render useful recommendations for policymakers.